The Effect of Learning Media and Teacher Supervision on the Learning Achievement of Class X Students of SMA Kemala Bhayangkari - Lenti Br Ginting; Eva Julyanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of learning media and teacher supervision on student achievement in class X SMA Kemala Bhayangkari. The research method used in this study is a quantitative method with the class action method. The population in this study were all students of SMAS BHAYANGKARI 2 RANTAUPRAPAT class X-IIS-1 and X-MIA-1, totaling 50 students divided into two classes, namely class control and experimental class. The sampling technique used is probability sampling using cluster sampling (area sampling). The instrument and data collection technique used in this study is a multiple-choice test to measure student achievement. The data analysis technique used is descriptive quantitative with descriptive statistics such as descriptive analysis, normality test, paired sample t-test, independent sample t-test on the results of pre-test and post-test then presented in the form of tables and graphs. Based on the results of the analysis, it is known that the average value of student learning outcomes before and after the application of learning media and teacher supervision on student achievement is 42.56 and 50.56% to 79.16% and 71.44%, respectively. The difference in student learning outcomes between the experimental class and the control class is 15.72% and the effect of learning media and teacher supervision on the learning achievement of class X students at SMA Kemala Bhayangkari is 36.6% and the ratio of improvement between the experimental class and the control class is 7.72%.